Analisis Kesulitan Siswa dalam Memecahkan Masalah Sistem Persamaan Linear Dua Variabel (SPLDV) Ditinjau dari Kesadaran Metakognisi - Rezki Hidayanti; Nurdin; Fajar (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2019)
This research aims to know description of students’ difficulties in solving problem of linear equation system with two variable viewed from metacognition awareness and factors that cause students’ difficulties in solving problem of linear equation system with two variable. The type of research is qualitative research with descriptive approach. Retrieval of subject perfomed by providing metacognition awareness questionnaire to students class IX and from result of metacognition awareness questionnaire selected purposively three subjects. Insrument in this research is questionnaire of Metacognitive Awareness Inventory (MAI) developed by Scraw & Dennison, diagnostic tes of difficulties in solving problem of linear equation system with two variable and interview guidelines. Indicathors of difficulties in solving problem namely understanding the problem, devising a plan, carrying out the plan, and looking back. Result of research show: 1)subject with high metacognition awareness difficulties in understanding the story problem. 2) Subject with moderate metacognition awareness difficulties in devising a plan, difficulties in carrying out the plan, and difficulties in looking back. 3) subject with low metacognition awareness experience most difficulty in solving problem. Subject difficulties in understanding the problem, difficulties in devising a plan, difficulties in carrying out the plan, and difficulties in looking back.